Geografija človeških virov v Sloveniji - pomen ustvarjalnih socialnih skupin za regionalni razvoj - Ravbar, Marjan (Geografski vestnik, 2007)
The article analyzes the spatial dispersion of creative occupations in various municipalities in Slovenia. The main conclusion, drawn from the articleis the very uneven distribution of creative occupations, which are most dominant in national employment centres and suburban areas of city regions. Creative social groups undoubtedly represent a strong impact on the regional development, which is seen through GDP per capita. The areas with higher levels of creative occupations are more innovative and their social and economic development more dynamic. The analyses also show a positive correlation between the share of employed people in creative occupations and innovativeness based on the average number of patents per capita.
Keywords: geografija; geography; regionalni razvoj; ekonomski razvoj; človeški viri; družbene skupine; ustvarjalnost; Slovenia; Slovenija